Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357178
|View full text |Cite
|
Sign up to set email alerts
|

Targeting across displayless space

Abstract: Multi-monitor displays and multi-display environments are now common. Cross-display cursor movement, in which a user moves the pointer from one display to another, occurs frequently in these settings. There are several techniques for supporting this kind of movement, and these differ in the way that they deal with displayless space (the physical space between displays). Stitching is the method used by most operating systems; in this technique, the cursor jumps from the edge of one display directly into the nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Transfer between such displays involves inherent displayless space i.e., the gap between coplanar displays. Further work showed that accounting for this space in motor-controlled input does not improve performance [Nacenta et al 2008]. In mobile settings, Touch Projector mapped touches from a smartphone, through its rear camera, to displays in the environment to enable remote interaction [Boring et al 2010].…”
Section: Cross-device Information Transfermentioning
confidence: 99%
“…Transfer between such displays involves inherent displayless space i.e., the gap between coplanar displays. Further work showed that accounting for this space in motor-controlled input does not improve performance [Nacenta et al 2008]. In mobile settings, Touch Projector mapped touches from a smartphone, through its rear camera, to displays in the environment to enable remote interaction [Boring et al 2010].…”
Section: Cross-device Information Transfermentioning
confidence: 99%
“…Finally, our own Ubiquitous Cursor research prototype is a precursor of ASPECTA which uses the same kind of hardware setup with the specific purpose of providing visual feedback for indirect input (e.g., mouse input) in what has been termed "displayless" space [30]. Although the ASPECTA toolkit inherits the hardware approach based on a hemispherical mirror, it is not constrained to it and it provides an API and configuration algorithm to enable the implementation of other, more generic, applications.…”
Section: Projection-based Environmentsmentioning
confidence: 99%
“…Finally, perspective cursor control requires the user to navigate display-less space blindly. However, recent research [7] has shown that warping the mouse pointer across large gaps between displays is superior to a mouse ether approach. This finding is particularly important for multi-user setups, which often employ spatially separated displays (e.g., a conference table in the center and surrounding wall displays).…”
Section: Cross-display Navigation Techniquesmentioning
confidence: 99%
“…To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. mance is affected by discontinuities in the spatial display arrangement [10,7] and the user's location within the environment [6,8]. Spatially consistent mouse pointer navigation techniques aim to accommodate for these discontinuities by creating cross-display transitions taking the spatial display arrangement into account.…”
Section: Introductionmentioning
confidence: 99%